2001
DOI: 10.1300/j027v19n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Service Utilization, and Treatment Costs Among Medicare Elderly: Gender Differences

Abstract: The results indicate that mood disorders, outpatient services, and total mental health costs are higher for females than males; however, total health care costs are higher for males than females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…In study carried out by Burns et al, total health care costs were higher for males than females [40]. In addition, Orueta et al [31] demonstrated that once adjusted per number of chronic conditions and socioeconomic characteristics, individual cost for females was lower than for males for all ages but in the range of 18–44 years old, as expected due to obstetric care.…”
Section: Discussionmentioning
confidence: 97%
“…In study carried out by Burns et al, total health care costs were higher for males than females [40]. In addition, Orueta et al [31] demonstrated that once adjusted per number of chronic conditions and socioeconomic characteristics, individual cost for females was lower than for males for all ages but in the range of 18–44 years old, as expected due to obstetric care.…”
Section: Discussionmentioning
confidence: 97%
“…11,[27][28][29] Patients with depression use more healthcare resources, including clinician visits and hospital admissions. 30,31 However, despite higher utilization rates, routine care such as screening may be overlooked. Patients and providers may be overly focused on managing the depression, or they may assume it is a natural consequence of events associated with aging, such as the loss of loved ones or medical illness, and appropriate proper treatment may not be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In non-Asian populations, elderly women on Medicare tend to utilize outpatient mental health services for depression more than elderly men on Medicare (Burns, Cain, & Hussaini, 2001; Husaini et al, 2002). In the last few years, studies have indicated potential gender differences in depressive symptoms and the rates of elderly individuals seeking depression treatment (Jang, Kim, & Chiriboga, 2010; Park et al 2013).…”
Section: Introductionmentioning
confidence: 99%